Organ‐on‐a‐Chip: A Heart‐Breast Cancer‐on‐a‐Chip Platform for Disease Modeling and Monitoring of Cardiotoxicity Induced by Cancer Chemotherapy (Small 15/2021). Issue 15 (15th April 2021) - Lee, Junmin; Mehrotra, Shreya; Zare‐Eelanjegh, Elaheh; Rodrigues, Raquel O.; Akbarinejad, Alireza; Ge, David; Amato, Luca; Kiaee, Kiavash; Fang, YongCong; Rosenkranz, Aliza; Keung, Wendy; Mandal, Biman B.; et al.
Abstract : In article number 2004258, Ali Khademhosseini, Su Ryon Shin, and co‐workers develop a model for investigating chemotherapy‐induced cardiotoxicity where induced pluripotent stem cell‐derived cardiac tissues are interacted with breast cancer tissues on a dual‐organ platform. Using electrochemical immuno‐aptasensors to monitor cell‐secreted multiple biomarkers, the proposed platform could be potentially suitable for early detection and prediction of cardiotoxicity in individual patients.